Capillary self-thinning of threads of polyelectrolyte solutions with axial electric fields - Patrick Martin; Gleb Vasilyev; Eyal Zussman; Alexander L. Yarin (Proceedings of the National Academy of Sciences, 2025)
A theory of solutions of charged polyelectrolyte (PE) macromolecules, treating them as electric dipoles, is proposed. In a thin thread of PE solution sustained between two disks—whether wettable or nonwettable—these dipoles are reoriented by an axial electric field, aligning themselves with the field direction. This alignment causes significant axial elastic stresses and affects capillary self-thinning dynamics of the thread, slowing the process and potentially arresting it entirely, and even leading to oscillatory regimes. Accordingly, the evolution of the thread radius deviates significantly from the exponential decay characteristic of solutions of flexible polymer macromolecules and the linear decay characteristic of Newtonian fluids. At relatively high electric field strengths, in a thread where elastic stresses become dominant, an oscillatory regime emerges. Here, the cross-sectional radius not only decreases but also increases and oscillates in time—a behavior rooted in an ill-posedness of the problem reducing to the Laplace equation in case of strong electric fields. This indicates a manifestation of Hadamard instability. The theory is supported by experimental data acquired in this work.